Late-Onset Nevus Comedonicus With Follicular Epidermolytic Hyperkeratosis—Case Report and Review of the Literature. (June 2019) - Zanniello, Ramona; Pilloni, Luca; Conti, Brunella; Faa, Gavino; Rongioletti, Franco
Abstract : Abstract: Nevus comedonicus is a rare cutaneous follicular hamartoma, characterized by the clustering of papules with firm, blackened horny buffers. It is usually present at birth or during childhood, although few cases of late-onset disease have been described. We present a case of postmenopausal-onset nevus comedonicus in a 55-year-old white woman without relevant medical history. Skin biopsy showed the typical features of several cyst-dilated follicular structures occupied by keratotic material and the peculiar finding of epidermolytic hyperkeratosis of the follicular epithelial walls. A brief review of the clinical and histological features of other similar cases published in the literature is performed.